Education Sector Public Expenditure Tracking and Service Delivery Survey in Zambia - World Bank Group (World Bank, Washington, DC, 2016)
The Public Expenditure Tracking Survey (PETS) and Quality Service Delivery Survey (QSDS) report is a product of a microscopic analysis of the performance of the Zambian Government in the education and skills sector. The report brings out independent viewpoints on the status of the education sector in Zambia; that is, it sheds light on the achievements that the sector has made in implementing the strategies and interventions intended to provide quality education service to the young citizens.